Ways of looking: an eye-tracking study of visual literacy expertise. Issue 1 (2nd January 2022) - Brumberger, Eva
Abstract: Eye tracking has been utilized for decades to study perceptual processes in a range of fields, and it has proven particularly useful for studying how the viewing behaviours of experts and novices within a field differ from one another. This article reports on a study that uses eye tracking to examine patterns in the ways that visual communication experts and non-experts read journalistic photographs that they might encounter in their daily lives. Expert participants (29) were practitioners with a minimum of 4–5 years of experience in a visual communication field; non-expert participants (29) had no training in visual communication and had 0–1 year of experience. Participants viewed 10 images and answered a series of four questions about each image. Participant eye movements were tracked utilizing a TobiiPro x2-60 eye tracker connected to a 17-inch high-end gaming laptop. The literature suggests that there should be observable differences between the eye movements of experts and non-experts, with expert viewing behaviour being more efficient and effective. However, the differences between experts and non-expert participants in the study were inconsistent and far less extensive than expected. The article discusses possible explanations for these results and suggests directions for future studies.